Domestication of medicinal plants (Lonicera japonica Thunb.) in China: comparison of morphological, resistance and biochemical traits between wild and cultivated populations - Hou, Congzhe; Huang, Luyao; Li, Zhuangzhuang; Sun, Nan; Yang, Sheng; Li, Jia; Liu, Zhenhua (Frontiers in Plant Science, 2025)
BackgroundMost studies on domesticated plants have focused on those utilized for sustenance purposes. This study provides valuable insights into the domestication processes of honeysuckle (Lonicera japonica Thunb.), a semi-evergreen twining vine in the Caprifoliaceae family that is important in traditional Chinese medicine for its flower buds and potential as a dietary supplement. The definition of domestication syndrome for honeysuckle remains unclear due to its perennial and asexual reproduction mode, resulting in a lack of information on domestication-related traits. Therefore, this study aims to compare and analyze differences in morphology, resistance, and biochemical composition between wild and cultivated varieties.MethodsA total of 36 wild and 81 cultivated specimens were examined to compare plant morphology, flowering time, bud length, active ingredients, and resistance between wild and cultivated populations.ResultsThe cultivated honeysuckle exhibited several noteworthy characteristics, including more erect plant morphology, higher flower-to-leaf ratio, more obvious aggregation of flowers into clusters at the top of branches, higher frequency of flowering, and longer bud length compared to the wild type. Additionally, the cultivated specimen demonstrated significantly elevated levels of chlorogenic acid as a biochemical constituent. However, in terms of resistance against powdery mildew, wild individuals displayed evident advantages over their cultivated counterparts.ConclusionThe observed phenotypic variation within the honeysuckle field provides empirical support for the hypothesis that farmer management practices influence domestication syndrome, as indicated by the deliberate enhancement of specific desirable traits during species domestication.